RW2 Alteration to the oral microbiome following dietary nitrate supplementation does not influence the vascular responsiveness to an acute nitrate dose. (May 2019) - Burleigh, Mia; Liddle, Luke; Monaghan, Chris; Muggeridge, David J; Sculthorpe, Nicolas; Butcher, John; Henriquez, Fiona; Easton, Chris
Abstract : Background: Nitrate (NO3 - ) contained in food and beverages can transiently increase nitric oxide (NO) availability following bacterial reduction to nitrite (NO2 - ) in the oral cavity. Increased levels of NO have been consistently shown to reduce blood pressure and elicit other favourable cardiovascular and metabolic effects. We have previously reported that regular ingestion of dietary NO3 - increases salivary pH and alters the abundance of bacteria that are responsible for NO3 - reduction. Purpose: The present study tested the hypothesis that these adaptations to the oral bacteria would improve the capacity of the mouth to reduce NO3 - to NO2 - and increase the vascular responsiveness to a NO3 - dose. Methods: Eleven healthy males received 7 days of supplementation with NO3 - -rich beetroot juice (BR). The acute responses following the ingestion of a bolus of BR were assessed before (day 0) and after (day 8) supplementation. Samples of saliva and blood were collected for the analysis of NO markers and vascular function was assessed by blood pressure and flow mediated dilation (FMD). Results: As previously reported, 7 days of supplementation with BR significantly altered the composition of the microbiome. Some species NO3 - -reducing bacteria increased in abundance and other, mostly pathogenic species, were reduced. The ingestion of BR on days 0 and 8 increased salivary and plasma NO2 -, decreased blood pressure, and increased the FMD response (all p<0.05). Despite the alterations to the microbiome, there was no difference in the magnitude of the changes in: salivary NO2 - (day 0 Δ 2182.3 µM±1788.8 µM, day 8 Δ 1370.1 µM±1833.8 µM), plasma NO2 - (day 0 Δ 314.3 µM±149.7 µM, day 8 Δ 173.4±122.7 µM), flow mediated dilation (day 0 Δ 1.75%±1.71%, day 8 Δ 1.65%±2.12%), mean arterial blood pressure (day 0 Δ −1 mmHg ±4 mmHg, day 8 Δ −3 mmHg ±3 mmHg). Conclusions: Supplementing the diet with BR alters the microbial composition of the tongue in favour of oral health and results in transient improvements in vascular function. Nevertheless, the adaptations to the microbiome do not enhance the capacity to generate NO from dietary NO3 - or the vascular responsiveness to an acute bolus of BR.